Raves, clubs and ecstasy: the impact of peer pressure - Baojun Song; Melissa Castillo-Garsow; Karen R. Ríos-Soto; Marcin Mejran; Leilani Henso; Carlos Castillo-Chavez (Mathematical Biosciences and Engineering)
Ecstasy has gained popularity among young adults who frequent raves and nightclubs. The Drug Enforcement Administration reported a 500 percent increase in the use of ecstasy between 1993 and 1998. The number of ecstasy users kept growing until 2002, years after a national public education initiative against ecstasy use was launched. In this study, a system of differential equations is used to model the peer-driven dynamics of ecstasy use. It is found that backward bifurcations describe situations when sufficient peer pressure can cause an epidemic of ecstasy use. Furthermore, factors that have the greatest influence on ecstasy use as predicted by the model are highlighted. The effect of education is also explored, and the results of simulations are shown to illustrate some possible outcomes.